Crystal structure of (4-bromobenzyl)triphenylphosphonium bromide ethanol solvate, C52H48Br4OP2 - Jiang, Jinke; Jiang, Hui (Zeitschrift für Kristallographie. New crystal structures, 2024)
Br OP , orthorhombic, (no. 56), = 20.173(5) Å, = 12.224(3) Å, = 18.858(5) Å, = 4650.2(19) Å , = 4, ) = 0.0395, ) = 0.0906, T = 289(2) K.